2014
DOI: 10.2478/pjvs-2014-0035
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the assessment of discharge accumulation in the lower airways and tracheal septum thickening in the differential diagnosis of recurrent airway obstruction (RAO) and inflammatory airway disease (IAD) in the horse

Abstract: The aim of the present study was to use endoscopic evaluation to compare the grade of accumulation of discharge in the lower airways of horses with recurrent airway obstruction (RAO) and inflammatory airway disease (IAD), and to estimate the usefulness of endoscopic evaluation in differential diagnosis of these diseases. Endoscopic evaluation consists of: the amount of discharge in the lower part of the trachea and tracheal bifurcation, and the assessment of tracheal septum thickness.This study was performed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 12 publications
1
15
0
1
Order By: Relevance
“…Endoscopic scoring of discharge accumulation in area of tracheal bifurcation was performed on the basis of a 4 grade scale which was developed during our earlier research (Wysocka and Kluciński 2014).…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Endoscopic scoring of discharge accumulation in area of tracheal bifurcation was performed on the basis of a 4 grade scale which was developed during our earlier research (Wysocka and Kluciński 2014).…”
Section: Animalsmentioning
confidence: 99%
“…Both diseases are characterized by cough, nasal discharge, accumulation of discharge in the airways and poor performance without an elevation of body temperature (Coultil et al 2007, Gerber et al 2009, Wysocka and Kluciński 2014.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These observations reinforce the importance of respiratory endoscopy as an effective diagnostic method, especially in horses mildly affected by chronic or sub-acute pathologies (BEECH, 1991). Also, a recent study demonstrated that endoscopic assessment of carina thickness and airway mucus is useful for diagnosing IAD and RAO (WYSOCKA & KLUCINSKI, 2014).…”
Section: Clinic and Surgerymentioning
confidence: 99%
“…Optimal airway function is essential for horses performing at high levels. It is common for subclinical respiratory diseases to go undetected on routine clinical examinations, often requiring auxiliary diagnostic methods (WYSOCKA & KLUCINSKI, 2014 (JCB), por meio de mensuração da pressão interpleural através da ventigrafia e endoscopia respiratória. Quando presentes nas vias aéreas, foram coletadas secreções por aspirado traqueal transendoscópico para realização de citologia.…”
Section: Introductionunclassified